2014
DOI: 10.1371/journal.pone.0111109
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Pulmonary Function and Emphysema Score Prognostic Index for Staging in Chronic Obstructive Pulmonary Disease

Abstract: IntroductionChronic Obstructive Pulmonary Disease (COPD) is characterized by high morbidity and mortality. Lung computed tomography parameters, individually or as part of a composite index, may provide more prognostic information than pulmonary function tests alone.AimTo investigate the prognostic value of emphysema score and pulmonary artery measurements compared with lung function parameters in COPD and construct a prognostic index using a contingent staging approach.Material-MethodsPredictors of mortality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Additional research is warranted to investigate the structural correlates of increased VD in mild COPD, e.g. microvascular disease [84], early emphysema [32,85,86], ventilation distribution heterogeneity [27,86]. Regardless of the mechanism(s), high V′E/V′CO 2 nadir is linked to earlier attainment of critical dynamic mechanical constraints: inspiratory reserve volume becomes critically reduced.…”
Section: Ventilatory Efficiency and Exercise Intolerancementioning
confidence: 99%
“…Additional research is warranted to investigate the structural correlates of increased VD in mild COPD, e.g. microvascular disease [84], early emphysema [32,85,86], ventilation distribution heterogeneity [27,86]. Regardless of the mechanism(s), high V′E/V′CO 2 nadir is linked to earlier attainment of critical dynamic mechanical constraints: inspiratory reserve volume becomes critically reduced.…”
Section: Ventilatory Efficiency and Exercise Intolerancementioning
confidence: 99%
“…Several studies have shown that an increased V D /V Tphys , partially due to emphysema [21,23,25,28,96,97], constitutes an important correlate of a high V′ E /V′ CO 2 . As discussed later, this is particularly true in patients who are not severely compromised from the mechanical standpoint, i.e.…”
Section: Structural and Functional Determinants Of V′ E /V′ Co 2 In Copdmentioning
confidence: 99%
“…However, no studies on the clinical impact of the ESI have been published. FEV 1 and other spirometric variables such as FEV 1 /FVC have been shown to correlate with all-cause mortality in several previous studies and are currently the principal spirometric measures used when establishing severity of airflow obstruction [4][5][6][7][8]. Since ESI is not dependent on reference values or any additional equipment beyond that needed for conducting spirometry, it could be easily implemented in a clinical setting alongside other currently used spirometric parameters such as FEV 1 .…”
Section: Introductionmentioning
confidence: 99%